(untitled) (ACTA MEDICA PERUANA, 2022)
Peru has been one of the countries most affected by the COVID-19 pandemic. After having suffered two devastating epidemic waves, the emergency department of the Edgardo Rebagliati Martins National Hospital maintained the challenge of constantly and dynamically preparing to face a third wave that has already hit many countries around the world. For this, the department prepared itself in all areas, to contribute to reducing the impact of the disease, guaranteeing not only the quality of care, but also the safety of health personnel, modulating the work and mental load generated by the pandemic over-demand. In this way, the department was better prepared when the third wave occurred. In conclusion, constant and dynamic preparation is essential to face the increase in cases; as well as to guarantee the safety and wellbeing of health personnel.